PENGEMBANGAN LKS BERCIRIKAN PROBLEM BASED LEARNING UNTUK SISWA SMP AR-ROHMAH MALANG KELAS VII - Ayu Rahayu; Gatot Muhsetyo; Swasono Rahardjo (Graduate School of Universitas Negeri Malang, 2016)
The research objective of this development is to produce mathematical Student Worksheet (LKS) is characterized by problem based learning to VII grade. In addition, this study also was conducted to determine the criteria LKS is generated based on the aspect of validity, practicality and effectiveness. The kind of research this is the development of research. The development of this research designed by following phases Plomp model of development, namely: prelimininary research, prototyping phase, and assesment phase. The subjects of this research is students of VII grade Ar-Rohmah junior high school Malang academic year 2015/2016 as many as 27 students. From the results of the field trials, found that LKS developed have valid criteria, practical, and effectiveTujuan penelitian pengembangan ini adalah untuk menghasilkan Lembar Kerja Siswa (LKS) matematika bercirikan pembelajaran berbasis masalah untuk kelas VII SMP. Selain itu, penelitian ini juga dilakukan untuk mengetahui kriteria LKS yang dihasilkan berdasarkan aspek kevalidan, kepraktisan dan keefektifan. Jenis penelitian ini merupakan penelitian pengembangan. Penelitian pengembangan ini dirancang dengan mengikuti tahap-tahap model pengembangan Plomp, yaitu: penelitian awal, tahap prototipe, dan tahap penilaian. Subjek penelitian ini adalah siswa kelas VII SMP Ar-Rohmah Malang tahun ajaran 2015/2016 sebanyak 27 siswa. Dari hasil uji coba lapangan, diperoleh bahwa LKS yang dikembangkan telah memenuhi kriteria valid, praktis, dan efektif.